Community Management Plan for Sustainability of Mangrove Ecosystem in Nuxco Lagoon, Guerrero, Mexico - Berenice, García-Domínguez Yarely; Laura, Sampedro-Rosas María; Benjamín, Castillo-Elías; Kai, Sonder; Herlinda, Gervacio-Jiménez; Ramón, Bedolla-Solano (International Journal of Geography and Geology, 2019)
Globally conservation of biodiversity and restoration of endangered species (specially the mangroves) has received much critical attention in sustainability studies of regional and tropical ecosystems. Sustainability succeeds when the economy of the region is improved without loss to biological diversity. This work presents a proposal to initiate a Community Management Plan for the sustainability of the Mangrove Ecosystem of Nuxco Lagoon, Guerrero, located in a rural community in the South of México. The objective was to create a proposal with the community called El Veinte, in order to conserve and avail of the environmental services that this ecosystem offers. The project was organized in three phases: Institutional Presentation through a preparatory workshop, Problem Identification, Action Plan. The data included opinions of key informants of the community sampled from municipal public services, staff of schools and individuals involved in key economic activities in the locality. Three topics were determined within the Community Management Plan: Investigation, Education and Preservation and short, medium and long term objectives were assigned to each topic. Through a consensus, the inhabitants of the rural community “El Veinte” identified three priority projects in order to improve the quality of life of the population with an approach of sustainability.